Ceftazidime-Avibactam Therapy Versus Ceftazidime-Avibactam-Based Combination Therapy in Patients With Carbapenem-Resistant Gram-Negative Pathogens: A Meta-Analysis - Li, Dan; Fei, Fan; Yu, Hua; Huang, Xiangning; Long, Shanshan; Zhou, Hao; Zhang, Jie (Frontiers in Pharmacology, 2021)
Objective: To systematically review and compare the efficacy and post-treatment resistance of Ceftazidime-avibactam therapy and ceftazidime-avibactam-based combination therapy in patients with Gram-negative pathogens. Methods: PubMed, Embase, Web of Science, CNKI, and WanFang data databases were searched from their inception up to March 31st, 2021 to obtain studies on ceftazidime-avibactam therapy versus ceftazidime-avibactam-based combination therapy in patients with carbapenem-resistant Gram-negative pathogens. The primary outcome was mortality rate, and the second outcomes were microbiologically negative, clinical success, the development of resistance after ceftazidime-avibactam treatment. Results: Seventeen studies with 1435 patients (837 received ceftazidime-avibactam-based combination therapy, and 598 received ceftazidime-avibactam therapy), were included in the meta-analysis. The results of meta-analysis showed that no statistically significant difference was found on mortality rate (Peto OR=1.03, 95% CI 0.79-1.34), microbiologically negative (OR=0.99, 95% CI 0.54-1.81), and clinical success (OR =0.95, 95% CI 0.64-1.39) between ceftazidime-avibactam-based combination therapy and ceftazidime-avibactam therapy. Although there was no difference in post-treatment resistance of ceftazidime-avibactam (OR=0.65, 95% CI 0.34-1.26), a trend favoring the combination therapy was found (according to the pooled three studies , OR=0.18, 95% CI 0.04-0.78). Conclusions: The current evidence suggests that ceftazidime-avibactam-based combination therapy may not have beneficial effects on mortality, microbiologically negative, and clinical success to patients with carbapenem-resistant Gram-negative pathogens. A trend of post-treatment resistance occurred more likely in ceftazidime-avibactam therapy than the combination therapy. Due to the limited number of studies that can be included, additional high-quality studies are needed to verify the above conclusions.